A new turtle from the Upper Cretaceous Bauru Group of Brazil, updated phylogeny and implications for age of the Santo Anastacio Formation - Menegazzo, Mirian Costa [UNESP]; Bertini, Reinaldo Jose [UNESP]; Manzini, Flavio Fernando [UNESP] (Elsevier B.V., 2015)
A new Podocnemidinura specimen from the Upper Cretaceous Bauru Group (Parana Basin) of southeastern Brazil was described. The Bauru Group provided an important portrait of the Brazilian Mesozoic terrestrial biota, which boasts a vertebrate fauna formed from fishes, frogs, lacertilians, crocodyliforms, dinosaurs and mammals; records of palynomorphs; and invertebrate fauna consisted of gastropods, bivalves, ostracods and conchostracans. Nevertheless, the age of these continental deposits is not precisely estimated, which prevents global correlations, and its fauna is argued to be endemic. The new specimen described is the first turtle from the Santo Anastacio Formation, and its morphological comparison with other South American forms provided a significant advancement in the understanding of the age of this unit (Late Cretaceous). This study permitted a revision of the turtle taxa of the Bauru Group. As a result, some taxa were considered synonym, including the new Santo Anastacio form. The specimen is still unnamed due to the absence of skull characters that preclude its accurate positioning within the Bauru Group skull-based taxa. In addition, the phylogenetic affinities of this taxon were analyzed into Podocnemidinura clade. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Pleurodira; Podocnemidinura; Bauru Group; Parana Basin; Upper Cretaceous